Cyprus : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2007)
This report reviews the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations on Anti-Money Laundering and Combating the Financing of Terrorism for Cyprus. The report highlights that the Cypriot authorities have demonstrated resolve to reduce the vulnerability of financial institutions and designated non-financial businesses and professions to money laundering. The Cyprus FIU (MOKAS) and the Central Bank of Cyprus have been particularly active in this respect. Since the Second Round Evaluation, both authorities were reinforced and are now adequately staffed.